Adult intussusception in diffuse large B-cell lymphoma following chemotherapy: A case report and literature review. (2016) - Hardjo Lugito, Nata Pratama; Kurniawan, Andree; Sebastian, Jeremy; Kusuma, Maria Lioni
Abstract: Secondary adult intussusception is associated with a pathological condition involving a lead point, including malignant tumors such as a primary or metastatic adenocarcinoma, GIST, leukemia, lymphoma, or carcinoid tumor. Thirty percent of small intestine intussusception was caused by malignancy. Most of these malignancies were metastases, while primary small intestinal malignancy were rare. Intussusception in lymphoma patients has been reported, with predominant location of intussusception in the ileo-colica region. Intussusception occuring after chemotherapy has been reported in four cancer patient following chemotherapy, but no report about this condition in lymphoma patient. A 44-year-old female patient with DLBCL was diagnosed of intussusception eight days after the initiation of chemotherapy. Plain abdominal radiology and CT scan confirmed intussusception on the ileo-colica region. No surgical intervention was done due to the condition of the patient. This is the first reported case of inssusception in a DLBCL patient that had undergone chemotherapy for the lymphoma.